"Not Just a Receiver": Understanding Patient Behavior in the Hospital Environment - Mishra, Sonali R; Haldar, Shefali; Pollack, Ari H; Kendall, Logan; Miller, Andrew D; Khelifi, Maher; Pratt, Wanda (Proceedings of the SIGCHI conference on human factors in computing systems. CHI Conference, 2016)
Patient engagement leads to better health outcomes and experiences of health care. However, existing patient engagement systems in the hospital environment focus on the passive receipt of information by patients rather than the active contribution of the patient or caregiver as a partner in their care. Through interviews with hospitalized patients and their caregivers, we identify ways that patients and caregivers actively participate in their care. We describe the different roles patients and caregivers assume in interacting with their hospital care team. We then discuss how systems designed to support patient engagement in the hospital setting can promote active participation and help patients achieve better outcomes.